Effect of Pregnancy on Selenium, Cupper ,Zinc and Others Biochemical Feacture (Baghdad Science Journal, 2013)
Pregnancy is a stressful condition in which many physiological and metabolic functions are altered to a considerable extent . Pregnancy is a physiological state accompanied by a high-energy demand and an increased oxygen requirement. The present study aim to study selenium ,zinc cupper in the first trimester of pregnancy. The study group comprised of Fourty five pregnant women and twenty six non pregnant women as control . The samples were taken from pregnant women who come to several heath center in Baghdad city to cheak up. Laboratory investigations including Cupper, Ceruloplasmin, Total Antioxidant (TAA), malondialdehyde (MDA), glutathione (GSH), Zinc, Uric acid, and Selenium had been measured in pregnant women and control . There were significant difference in Cupper, Selenium, Ceruloplasmin, TAA, Zinc, GSH, and MDA, in the pregnant women whene compared to control group. In this study, a significantly positive association was observed between zinc [mg/dl] with ceruloplasmin [mg/dl] (R = 0.47 p< 0.01 ) and TAA [mmol/l] (R= 0.42 p< 0.05) , and negative association was observed between zinc [mg/dl]and cupper [mg/dl] (R = 0.602, p< 0.01) , a significantly negative association between ceruloplasmin [mg/dl] with cupper [mg/dl] (R = 0.754, p< 0.01) ,and positive with TAA [mmol/l]( R = 0.562 p